Nanosized zinc oxide (n-ZnO) particles pretreatment to alfalfa seedlings alleviate heat-induced morpho-physiological and ultrastructural damages. (15th June 2022) - Kareem, Hafiz Abdul; Hassan, Mahmood Ul; Zain, Muhammad; Irshad, Annie; Shakoor, Noman; Saleem, Sana; Niu, Junpeng; Skalicky, Milan; Chen, Zhao; Guo, Zhipeng; Wang, Quanzhen
Abstract: Global efforts are in rapid progress to tackle the emerging conundrum of climate change-induced heat stress in grassland ecosystems. Zinc oxide nanoparticles (n-ZnO) are known to play a crucial role in plants' abiotic stress regulation, but its response in alfalfa against heat stress has not been explored. This study aimed at assessing the effects of n-ZnO on alfalfa under heat stress by various morpho-physiological and cellular approaches. Five-week-old alfalfa seedlings were subjected to foliar application of n-ZnO as a pretreatment before the onset of heat stress (BHS) to evaluate its effect on heat tolerance, and as a post-treatment after heat stress (AHS) to evaluate recovery efficiency. In vitro studies on Zn release from n-ZnO by Inductively coupled plasma mass spectroscopy (ICPMS) disclosed that the particle uptake and Zn release were concentration dependent. The uptake and translocation of n-ZnO examined by transmission electron microscope (TEM) reveling showed that n-ZnO was primarily localized in the vacuoles and chloroplasts. TEM images showed that ultrastructural modifications to chloroplast, mitochondria, and cell wall were reversible by highest dose of n-ZnO applied before heat stress, and damages to these organelles were not recoverable when n-ZnO was applied after heat stress. The results further enlightened that 90 mg L −1 n-ZnO better prevented the heat stress-mediated membrane damage, lipid peroxidation and oxidative stress by stimulating antioxidant systems and enhancing osmolyte contents in both BHS and AHS. Although, application of 90 mg L −1 n-ZnO in BHS was more effective in averting heat-induced damages and maintaining better plant growth and morpho-physiological attributes compared to AHS. Conclusively, foliar application of n-ZnO can be encouraged as an effective strategy to protect alfalfa from heat stress damages while minimizing the risk of nanoparticle transmission to environmental compartments, which could happen with soil application. Graphical abstract: Image 1 Highlights: The n-ZnO stimulated morpho-physiological responses in alfalfa under heat stress. Release of Zn from n-ZnO confirmed by ICPMS, and presence in leaves by TEM. The n-ZnO triggered antioxidant system sheltered alfalfa from oxidative damage. Gas exchange traits and osmolyte agents improved cell microstructure by n-ZnO. Results applicable for sustainable nanoparticle approaches to mitigate heat stress.